Ultrasound-guided perineural injection with dextrose for treatment of radial nerve palsy: A case report. Issue 23 (June 2018) - Chen, Si-Ru; Shen, Yu-Ping; Ho, Tsung-Yen; Chen, Liang-Cheng; Wu, Yung-Tsan
Abstract: Rationale: Perineural injection with dextrose could be a novel intervention for peripheral entrapment neuropathy. However, this intervention has not been reported for treating radial nerve palsy (RNP). Here, we present a case with RNP having outstanding improvement after 2 sessions of ultrasound-guided perineural injection with 5% dextrose (D5W). Patient concerns: A 62-year-old woman presented with difficulty and weakness in extension of her left wrist and fingers after she slept with the arm compressed against her body. Diagnoses: On the basis of the findings of electrophysiological study and ultrasonography, the RNP with axonal injury was diagnosed. Interventions: Initially, the patient received 2-months conservative treatments without any improvement. Two sessions of ultrasound-guided perineural injection with total 15cc D5W with an interval of 1 month were performed 2 months after symptom onset. Outcomes: A noteworthy improvement in sensory and motor functions was observed after ultrasound-guided perineural injection with D5W. Lessons: This case shows that ultrasound-guided perineural injection with D5W may be an effective and novel intervention for RNP.